Optimization of Bhabinkamtibmas Performance in the Framework of Maintaining Public Security and Order in the Legal Area of Karanganyar Police - Kevin Rosaldo Aritonang (Tanggon Kosala, 2023)
This research is based on the increasing number of disturbances to security and public order in the Karanganyar Police area. Bhabinkamtibmas has made pre-emptive efforts but the number of security disturbances has continued to increase. Therefore this research was conducted which aims to analyze and explain the performance of Bhabinkamtibmas in order to maintain security and public order. This research was conducted with a qualitative approach. Data collection was carried out by means of interviews, observation, and document studies. The theory used is the theory of Management (SDO), Performance, SWOT and the Optimization Concept, Bhabinkamtibmas and Kamtibmas. The results found that Bhabinkamtibmas in carrying out its duties in maintaining Kamtibmas had not gone as expected. This is conditioned by several obstacles in the form of a lack of quality human resources, budget and equipment for Bhabinkamtibmas. The conclusion is that the performance of Bhabinkamtibmas in the context of maintaining security and order has not been optimal due to the quality and performance of personnel who are still considered lacking and, the authors suggest that Bhabinkamtibmas personnel can try to apply for KEP Numbers to non-definitive personnel, add facilities and infrastructure and transportation budget so that the implementation of their duties can run optimally.